2001
DOI: 10.1159/000050024
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of pp65 in in vitro Generated pp65-Positive Polymorphonuclear Cells Mediated by Phagocytosis and Cell Fusion?

Abstract: Objective: The cytomegalovirus (CMV) antigenemia consists of the detection of CMV pp65 in the nucleus of polymorphonuclear granulocytes (PMN), but it is unclear where and how PMN pick up virus particles or proteins. In an in vitro model for CMV antigenemia we investigated the mechanism of pp65 uptake by PMN that results in its expression in the nucleus. Methods: A series of inhibitors of different mechanisms was used to study the uptake of pp65 by PMN during coculture with CMV-infected endothelial cells and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Moreover, neutropenia can raise difficulties to perform this technique due to the fact that antigenemia requires a sufficient number of neutrophils to detect CMV viral antigen. CMV causes an abortive replication within neutrophils and leads to uptake of antigen in perinuclear area (Kas-Deelen et al, 2001) which can be detected by use of monoclonal antibodies against pp65-antigen. Either fluorescent or enzyme labelled conjugate can be used to reveal the reaction.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Moreover, neutropenia can raise difficulties to perform this technique due to the fact that antigenemia requires a sufficient number of neutrophils to detect CMV viral antigen. CMV causes an abortive replication within neutrophils and leads to uptake of antigen in perinuclear area (Kas-Deelen et al, 2001) which can be detected by use of monoclonal antibodies against pp65-antigen. Either fluorescent or enzyme labelled conjugate can be used to reveal the reaction.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…We previously postulated that HCMV might employ MNC and PMN as a vehicle for its dissemination through the body (15,21). Using clinical isolates of HCMV, we and others have shown that PMN and MNC can acquire infective HCMV in vitro by coculture on infected cells.…”
mentioning
confidence: 92%
“…Using clinical isolates of HCMV, we and others have shown that PMN and MNC can acquire infective HCMV in vitro by coculture on infected cells. Subsequently, these leukocytes were able to retransmit the virus to uninfected cells (10,14,15,19,25). The presence of intact viral particles in these leukocytes could also be demonstrated with electron microscopy (10,15,19).…”
mentioning
confidence: 96%
See 2 more Smart Citations